Information and Technology for Human and Children's Rights - Halpin, Edward F; Hick, Steve (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The research work underlying this paper has been undertaken over a number of years and resulted in the publication of the book 'Human Rights and the Internet', which provides a unique overview of the subject. This paper examines the use of information, using the application of the Internet and information and communication technology (ICT), in the context of human and children's rights and relates to two of the themes of the conference - technology and people.